Molecular understanding for large deformations of soft bottlebrush polymer networks - Cai, Li-Heng (Soft matter, 2020)
Networks formed by crosslinking bottlebrush polymers are a class of soft materials with stiffnesses matching that of 'watery' hydrogels and biological tissues but contain no solvents. Because of their extreme softness, bottlebrush polymer networks are often subject to large deformations. However, it is poorly understood how molecular architecture determines the extensibility of the networks. Using a combination of experimental and theoretical approaches, we discover that the yield strain γ y of the network equals the ratio of the contour length L max to the end-to-end distance R of the bottlebrush between two neighboring crosslinks: γ y = L max / R − 1. This relation suggests two regimes: (1) for stiff bottlebrush polymers, γ y is inversely proportional to the network shear modulus G , γ y ∼ G −1 , which represents a previously unrecognized regime; (2) for flexible bottlebrush polymers, γ y ∼ G −1/2 , which recovers the behavior of conventional polymer networks. Our findings provide a new molecular understanding of the nonlinear mechanics for soft bottlebrush polymer networks. We discover a new regime in which the extensibility of bottlebrush polymer networks is inversely proportional to the network stiffness.